2015
DOI: 10.11648/j.ijll.20150305.16
|View full text |Cite
|
Sign up to set email alerts
|

Internal and External Factors Affecting Learning English as a Foreign Language

Abstract: This study investigated the effects of internal and external factors on learning English as a foreign language from Iranian EFL learners' points of view. Copies of a 30-item Lickert-scale questionnaire, addressing internal and external factors or principle components, were distributed among about 140 postgraduate students of ELT in three universities in Iran. The collected data were then subjected to Principle Component Analysis (PCA). The findings revealed that while internal and external components are disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 14 publications
1
19
0
3
Order By: Relevance
“…Internal factors imply -167 -cognitive and affective factors such as motivation, intelligence, anxiety, risk-taking and ability. Many studies have confirmed that motivation correlates strongly with proficiency, indicating both that successful learners are motivated and that success improves motivation (Mahmoudi & Mahmoudi, 2015). Siegel in Mahmoudi and Mahmoudi state motivation is affected by learners' attitudes toward the second language, its speakers, and the speakers' culture (Mahmoudi & Mahmoudi, 2015).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Internal factors imply -167 -cognitive and affective factors such as motivation, intelligence, anxiety, risk-taking and ability. Many studies have confirmed that motivation correlates strongly with proficiency, indicating both that successful learners are motivated and that success improves motivation (Mahmoudi & Mahmoudi, 2015). Siegel in Mahmoudi and Mahmoudi state motivation is affected by learners' attitudes toward the second language, its speakers, and the speakers' culture (Mahmoudi & Mahmoudi, 2015).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Internal factors are factors which come from inside the individual. Internal factors imply cognitive and affective factors such as motivation, intelligence, anxiety, risk-taking and ability (Mahmoudi & Mahmoudi, 2015). Many studies have confirmed that motivation correlates strongly with proficiency, indicating both that successful learners are motivated and that success improves motivation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations